2019
DOI: 10.1111/cei.13388
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine modulates molecules of the innate immune response in epithelial cells and macrophages during infection withM. tuberculosis

Abstract: Summary Smoking increases susceptibility to becoming infected with and developing tuberculosis. Among the components of cigarette smoke, nicotine has been identified as the main immunomodulatory molecule; however, its effect on the innate immune system is unknown. In the present study, the effect of nicotine on molecules of the innate immune system was evaluated. Lung epithelial cells and macrophages were infected with Mycobacterium tuberculosis (Mtb) and/or treated with nicotine. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 54 publications
1
26
0
2
Order By: Relevance
“…However, in MAP-infected macrophages, nicotine has significantly decreased expression of both TLR2 and TLR4 . Although similar observations were reported in MTB-infected macrophages derived monocyte (MDMs) and in lung epithelial cells [ 34 , 38 ], this is the first data to show a negative effect for nicotine on TLR2 expression in macrophages infected with MAP. We are still uncertain about the impact of this observation on MAP viability and burden in macrophages.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, in MAP-infected macrophages, nicotine has significantly decreased expression of both TLR2 and TLR4 . Although similar observations were reported in MTB-infected macrophages derived monocyte (MDMs) and in lung epithelial cells [ 34 , 38 ], this is the first data to show a negative effect for nicotine on TLR2 expression in macrophages infected with MAP. We are still uncertain about the impact of this observation on MAP viability and burden in macrophages.…”
Section: Discussionsupporting
confidence: 87%
“…Recent reports suggested the involvement of TLR2 in MTB infection especially with cell wall derivatives [ 33 , 34 ]. Other study showed that TLR2-deficient mice failed to develop immune response against MTB [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACh has not been studied in a pulmonary TB context. However, several studies have demonstrated that nicotine, a major constituent of cigarette smoke, worsens disease outcomes through nAChR stimulation ( 15 17 ). Additionally, receptors involved in the PPIR are implicated in the pathogenesis of active TB ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Это происходит как в результате непосредственного токсического воздействия компонентов табачного дыма на клетки бронхов и легкого, иммунной системы, так и влияя на фармакокинетику противотуберкулезных препаратов [3]. Кроме того, исследования влияния никотина на эпителиальные клетки легких и макрофагов, инфицированных Mycobacterium tuberculosis, показали, что никотин снижает экспрессию Toll-подобных рецепторов TLR-2, TLR-4 и NOD-2 в клетках, а также продуцирование белка сурфактанта SP-D в пневмоцитах типа II, уменьшает выработку интерлейкина (IL-6) [4].…”
Section: Introductionunclassified